2013
DOI: 10.1088/0953-4075/46/9/095701
|View full text |Cite
|
Sign up to set email alerts
|

Excitation cross sections for Li3 +, Ne10 +and Ar18 ++H(1s) collisions of interest in fusion plasma diagnostics

Abstract: We have calculated state-selective excitation cross sections in fully stripped Li3 +, Ne10 + and Ar18 ++H(1s) collisions from low (1 keV/amu) to high (1000 keV/amu) impact energies, relevant in fusion plasma diagnostics. In order to cover this broad impact energy range, three different theoretical methods have been employed: the semi-classical molecular and one-centre atomic-orbital close-coupling approaches, and the classical trajectory Monte Carlo method. Recommended partial excitation cross sections are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 52 publications
5
24
2
Order By: Relevance
“…The work by Agueny et al [19] was based on the two-center atomic orbital close-coupling method with Gaussian-type orbitals (TC-AOCC-GTO). Only excitation of the n = 2 and n = 3 shells are presented, since transition to higher energy states are not important at these impact energies [18]. It is shown that the present TC-BGM results are in satisfactory agreement with previously reported cross sections [18,19].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The work by Agueny et al [19] was based on the two-center atomic orbital close-coupling method with Gaussian-type orbitals (TC-AOCC-GTO). Only excitation of the n = 2 and n = 3 shells are presented, since transition to higher energy states are not important at these impact energies [18]. It is shown that the present TC-BGM results are in satisfactory agreement with previously reported cross sections [18,19].…”
Section: Resultssupporting
confidence: 86%
“…Only excitation of the n = 2 and n = 3 shells are presented, since transition to higher energy states are not important at these impact energies [18]. It is shown that the present TC-BGM results are in satisfactory agreement with previously reported cross sections [18,19].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In particular, the use of improved initial distributions has allowed to evaluate state selective CX cross sections for several systems [30][31][32][33], which have been merged with semiclassical calculations to provide sets of recommended data. This method has been recently applied to calculate excitation cross sections in [34]. The CTMC method has also been applied to study collisions with excited atoms (e.g.…”
Section: +mentioning
confidence: 99%